An Overview of Junior High School Students’ Knowledge and Preparedness in Facing Natural Disasters : Original Article - Hidayati, Nur; Sholikhah, Mar'atus; Hanafi , Aprelia Afidatul; Othman, Hamidah (Babali Publisher, 2024)
Introduction: Glagah is one of the districts in Lamongan Regency with a high potential for natural disasters such as floods, tornadoes, droughts, and forest fires. To reduce the impact of disasters, disaster mitigation is required. On the other hand, students are a vulnerable group to natural disasters. Before disaster mitigation is carried out, it is necessary to initially identify students’ level of disaster knowledge and preparedness. The purpose of the study was to determine students’ knowledge and preparedness in facing natural disasters. Method. The study used descriptive quantitative research with a sample of 310 junior high school students in Glagah District who were obtained using a two-stage cluster random sampling technique on March 6-10, 2024. The data were collected using a questionnaire on knowledge and preparedness for floods, tornadoes, and fires, and then analyzed descriptively. Result. The results indicated that students’ knowledge in dealing with floods, tornadoes, and fires was in the